The Selection of Suppliers of Ready Mix Concrete Raw Materials Using the Fuzzy AHP Method (The Case Studies: Sadawarna Dam Construction Project Package 1) - Hajar Kamilah; Kristianto Usman; Dian Perwitasari (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2023)
The construction of facilities such as buildings, roads, and dams has an important part role in supporting daily life activities. One of all the facilities currently being built is the Sadawarna Dam Construction Project Package 1. Where does the project function to supply the needs of water resources and irrigation in West Java. However, in the construction process the project has encountered obstacles such as delays in the delivery of raw materials by the suppliers which caused the casting time to be delayed. The solution to these problems can be found by the improvement the supplier selection method. One of the methods that can be used is the Fuzzy Analytical Hierarchy Process (Fuzzy-AHP). Where in the process will expand measuring tools in the selection decisions that involve expert respondent. As The variables in determining suppliers use 4 criteria such as price, delivery, quality, and location as well as 7 sub-criteria such as payment methods, bid prices, delivery times, delivery of flexibility, delivery of capacity, consistency of quality, and specification conformance. From these variables, a comparison value with the AHP scale will be obtained which will be converted into a Triangular Fuzzy Number (TFN) scale. The results of this research obtained the best criteria is quality and sub-criteria is the bid price, as well as the best alternative from the selection of suppliers of concrete raw materials suppliers of fine aggregate materials is CV BTP Cimalaka at 51.3% and suppliers of coarse aggregate materials are PT Fajar Mandiri at 63.7%.